Enhancing Paragraph Structure through Genre Awareness in Writing: An Experimental Study with Vocational Students - Alfridha Dwi Putri (PT Akselerasi Karya Mandiri, 2024)
Abstract This study examines the impact of genre-based instruction on the writing skills of vocational high school students, specifically focusing on paragraph organization, coherence, relevance, and vocabulary acquisition. A quasi-experimental design with pretest-posttest measures was employed, involving 60 students divided into an experimental group, which received genre-focused instruction, and a control group, which followed traditional writing instruction. The genre-based approach was tailored to the students' technical fields, emphasizing structured paragraph development, use of cohesive devices, topic relevance, and application of field-specific vocabulary. The results showed significant improvements in the experimental group across all four writing components, with mean posttest scores rising substantially compared to the control group. The experimental group’s standard deviations also decreased, indicating greater consistency in their writing performance. Paired t-tests confirmed that genre-based instruction led to statistically significant gains in organization, coherence, relevance, and vocabulary acquisition (p < 0.001). In contrast, the control group demonstrated minimal improvement. These findings support genre theory, suggesting that explicit genre instruction enhances both the quality and reliability of students’ writing. This study underscores the importance of integrating genre-based strategies into vocational curricula, as it equips students with the technical and professional writing skills needed for their careers. Future research could further explore the long-term effects of genre-based instruction across various vocational disciplines.